Analisis Kebijakan Penyaluran Dana Desa dalam Upaya Peningkatan Kesejahteraan Masyarakat Desa - Lenny Fatmasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Villages have a very important role in development in Indonesia, so the role of villages in development must be recognized and developed to ensure the achievement of welfare and progress of the village community. In running the government in a village, the village government certainly requires a number of funds. In Law Number 6 of 2014 concerning Villages, it is stated that villages have sources of income in the form of original village income, budget allocations from the State Budget (APBN), part of the results of regional taxes and regional levies of districts/cities, Village Fund Allocations which are part of the balancing funds received by districts/cities, financial assistance from the provincial APBD and district/city APBD, grants and donations that are not included from third parties, and other legitimate village income. As an implementing regulation of Law 6 of 2014 concerning Villages, the Government issued Government Regulation Number 60 of 2014 as amended by Government Regulation Number 22 of 2015 concerning Village Funds Sourced from the State Budget. Village Funds are funds sourced from the APBN which are allocated for villages that are transferred through the district/city APBD and are used to finance the implementation of government, implementation of development, community training, and community empowerment.